A novel unified model of keyhole plasma arc welding. (April 2019) - Li, Yan; Wang, Ling; Wu, Chuansong
Graphical abstract: Highlights: Keyhole-mode plasma arc welding was modeled with less computational resources and time. Coupled electro-magneto-thermal-mechanical mechanism was revealed. A dynamic arc pressure evolution was developed to present the keyhole process. The arc was compressed by the nozzle, shielding gas and electromagnetic force. Both heat flux and arc pressure mainly concentrate within a radius of 4 mm. Abstract: Keyhole plasma arc welding (PAW) has great potential in the advanced manufacturing industry. Previous research on PAW mainly concerns heat transfer in workpiece without plasma arc. Only several researchers constructed unified models of plasma arc and weld pool to investigate the keyhole welding process by Volume of Fluid (VOF) technique, while it takes too much computational time and resources. A novel unified heat transfer model was developed to demonstrate the keyhole-mode heat transfer in weld pool avoiding the cumbersome VOF technique. With a simple tip to exert the arc pressure calculated from plasma arc region into the weld pool, the model presents equivalent effects like a keyhole model. Electro-magneto-thermal conversion and the resulting thermal-mechanical interaction between plasma arc and weld pool are revealed. Heat flux and arc pressure both display a Gaussian distribution on the workpiece surface, and metal within r  = 4 mm is mostly affected. Weld pool gradually increases into a "reversed bugle-like" configuration due to the coupled thermal-mechanical effects from plasma arc. Two opposite circular flows appear at the bottom and the top edge of weld pool, which are dominated by the plasma arc force and Marangoni force, respectively. Calculated arc pressure distributions generally coincide with experimental results and previous research, and calculated weld pool geometry agrees well with experimental result, as well as the time for full penetration welding. The new model shows quite good applicability and simplicity.